Fatherlessness as a Risk Factor for Suicide among Nursing Students in Indonesia: An Attachment Theory Perspective - Fatin Karimatunnisa; Meida Laely Ramdani; Suci Ratna Estria; Wahyu Riyaningrum (Universitas Pahlawan Tuanku Tambusai, 2026)
Suicide is the third leading cause of death among young people worldwide. Contributing factors including family dysfunction and weak parent–child attachment. One prominent issue is the loss of a father’s role, either physically or emotionally, known as fatherlessness. This condition can hinder emotional regulation and increase vulnerability to mental health problems. Nursing students represent a high-risk group due to academic and clinical pressures. This study aimed to analyze the relationship between the level of fatherlessness and suicide risk among nursing students based on attachment theory. A quantitative cross-sectional design was used with 351 respondents selected through purposive sampling. The instruments included the Nurturant Father Involvement and Reported Father Involvement scales to measure fatherlessness, and the Suicide Behavior Questionnaire Revised (SBQ-R) to assess suicide risk. Results showed a significant relationship between fatherlessness and suicide risk (p < 0.001) with a moderate strength of association (Cramer’s V = 0,273). These findings emphasize that secure attachment as a protective factor for emotional well-being and highlight of paternal involvement as part of preventive efforts to reduce suicide risk among nursing students. Practical implications include educational institutions conducting family-based mental health screenings and educating on fathers’ caregiving importance to prevent suicide